Combination of mulberry leaf active components possessed synergetic effect on SD rats with diabetic nephropathy by mediating metabolism, Wnt/β-catenin and TGF-β/Smads signaling pathway. (28th June 2022) - Ji, Tao; Wang, Juan; Xu, Zhuo; Cai, Hong-Die; Su, Shu-lan; Peng, Xin; Ruan, Hong-Sheng
Abstract: Ethnopharmacological relevance: Mulberry leaf has attracted much attention due to its excellent curative effect on diabetes and its complications, whether the combination of its effective components have protective and synergistic effect on diabetic nephropathy (DN) in vivo remain unclear. Aim of the study: The aim of this study was to investigate the protective and synergistic effect of the combination (MAF1:1 and MAF1:5 ) of mulberry leaf alkaloids (MA) and flavonoids extract (MF) on DN. Materials and methods: A step by step method consisted of network pharmacological prediction, animal in vivo validation and metabolic mechanism research was used to construct the multi-component-target-pathway network of mulberry leaf against DN. Firstly, the potential components and mechanism of mulberry leaf against DN was explored by network pharmacology analysis. Secondly, DN animal model was established to validate the anti-DN activity of these potential compounds. Thirdly, the metabolomics of serum and urine samples from animal experiments was analyzed to explore the anti-DN mechanism of these potential compounds. Results: The results of network pharmacology demonstrated that a total of 7 compounds detected in MA and MF exhibited anti-DN activity, their mechanism were strongly in connection with metabolic pathways, arachidonic acid metabolism, sphingolipid signaling pathway, etc. The results of animal experiment indicated that MAF1:1 and MAF1:5 significantly relieved metabolic disorders through regulating Wnt/β-catenin and TGF-β/Smads signaling pathway, just like MF or MA alone. Metabolomics suggested they could regulate 16 serum and 7 urine endogenous metabolites through arachidonic acid metabolism, phenylalanine metabolism and sphingolipid metabolism, thus alleviated DN. Significantly, MAF1:1 and MAF1:5 might possess synergistic effect considering their therapeutic effects on DN rats were superior to the single use of MA or MF. Conclusions: MAF1:1 and MAF1:5 possessed protective and synergistic effect on DN rats through multi-target and multi-pathways. These findings were of great scientific significance and application value to reveal the advantage of mulberry leaf in preventing and treating DN. Graphical abstract: Image 1